Anales de la Facultad de Medicina 1995-2015: analysis and perspectives of its scientific role in Peru - Pacheco Romero, José (2015)
First published in 1918, Anales de la Facultad de Medicina is the official journal of San Fernando Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Following some years of absence, Anales was again published in 1995, under the direction of Dean José Piscoya Arbañil. Most of the Editorial Staff was later included in the new Editorial Committee in 2000 under the direction of José Pacheco Romero. Permanence, punctuality, visibility and impact distinguished the 15 years of administration of the journal despite editorial and financing limitations. Anales has received support from all the Faculty of Medicine Deans and the University Research Vice-Rector. It has obtained important indizations, and has digitized all journal articles and their respective doi since 1918, allowing more visits, article discharges and citations.